Size efficiency, splits and merger gains, and centralized resource reallocation of Spanish public universities. (June 2022) - Contreras, I.; Lozano, S.
Abstract: In this paper, the Spanish public university system is thoroughly analyzed in order to maximize its efficiency. First, the current technical and size efficiency of the different universities is assessed and those that should be split are identified. In a second phase, bearing in mind that it is the regional governments that supervise and control the public universities in Spain, the gains from potential mergers of universities within each Spanish region are individually evaluated. The third and last phase consists of reallocating the transferable resources between the universities within each region. The efficiency gains provided by each of these phases are quantified and added up, which leads to a significant efficiency improvement and a revised, optimal sector structure. Highlights: An estimation of size-efficiency is obtained through the computation of DEA models. Potential mergers and splits of individual universities are studied. An optimal structure for the Spanish public university system is developed.